Mutations in orthologous PETALOSA TOE-type genes cause a dominant double-flower phenotype in phylogenetically distant eudicots. (21st January 2020) - Gattolin, Stefano; Cirilli, Marco; Chessa, Stefania; Stella, Alessandra; Bassi, Daniele; Rossini, Laura
Abstract : A conserved mechanism regulates the dominantly inherited double-flower trait, and involves natural allelic variation at the microRNA172 binding site in the novel PETALOSA subclade of TARGET OF EAT (TOE)-type genes. Abstract: The double-flower phenotype has been selected by humans for its attractiveness in various plant species and it is of great commercial value for the ornamental market. In this study we investigated the genetic determinant of the dominant double-flower trait in carnation, petunia, and Rosa rugosa, and identified mutant alleles of TARGET OF EAT (TOE)-type genes characterized by a disruption of the miR172 target sequence and of the C-terminal portion of the encoded protein. Despite the phylogenetic distance between these eudicots, which diverged in the early Cretaceous, the orthologous genes carrying these mutations all belong to a single TOE-type subgroup, which we name as PETALOSA ( PET ). Homology searches allowed us to identify PET sequences in various other species. To confirm the results from naturally occurring mutations, we used CrispR-Cas9 to induce lesions within the miR172 target site of Nicotiana tabacum PET genes, and this resulted in the development of supernumerary petaloid structures. This study describes pet alleles in economically important ornamental species and provides evidence about the possibility of identifying and engineering PET genes to obtain the desirable double-flower trait in different plants.